Ultrasonography of the scrotum: Revisiting a classic technique. Issue 145 (December 2021) - Tsili, Athina C.; Bougia, Christina K.; Pappa, Ourania; Argyropoulou, Maria I.
Highlights: Grayscale and CDUS is the primary technique for the assessment of acute scrotum. Conventional US is accurate in the detection, localization and characterization of scrotal masses. Small, impalpable testicular tumors, detected incidentally on US are mostly benign. Abstract: Conventional US is the primary imaging modality for the evaluation of the scrotum, due to its high resolution, availability, cost-effectiveness and absence of ionizing radiation. Grayscale and color Doppler US provide a comprehensive assessment of scrotal diseases. The technique represents the mainstay for imaging of acute scrotum. US is highly accurate in the detection, localization and characterization of scrotal masses. Multiparametric US, including conventional US, contrast-enhanced US and tissue elastography has improved the diagnostic performance of the technique in the assessment of testicular diseases. MRI represents a valuable supplemental imaging tool for the investigation of scrotal pathology, mainly recommended in cases of indeterminate US findings. Recommendations recently issued by the European Society of Urogenital Radiology Scrotal and Penile Imaging Working Group (ESUR-SPIWG) refer to the use of scrotal sonography for the evaluation of pathologic entities, including testicular microlithiasis, small, non-palpable incidentally detected testicular masses, varicocele and scrotal trauma. In this review, the technical specifications for scrotal US and the normal sonographic findings are presented. Grayscale and color Doppler US findings of common acute scrotal diseases and scrotal masses are discussed. The complimentary role of multiparametric US and scrotal MRI is addressed. ESUR-SPIWG's guidelines are also reviewed.